Perancaangan Sistem Informasi Apotik Berbasis Web: Optimalisasi Layanan Pelanggan - Reihan Deirengga Batubara (Journal of Information System and Education Development, 2024)
This research discusses the development and implementation of a "Web-Based Pharmacy Information System" which aims to improve the efficiency of customer service and drug inventory management. By using web technology, PHP programming language, and MySQL database, this system allows pharmacies to monitor drug stocks in real-time, manage patient information, and provide integrated services. The use of PHP and MySQL in developing this application allows the automation of administrative tasks, including drug stock tracking, orders, and patient data management. This system also facilitates customer service with easy access to drug information and online drug ordering services. The research results show that the implementation of the Web-Based Pharmacy Information System has succeeded in increasing pharmacy efficiency, reducing drug stock shortages, and improving customer service. This system supports integrated drug management by integrating patient data, drug stock and customer service in one platform. Overall, this system illustrates how the use of web, PHP, and MySQL technologies can optimize customer service and medication inventory management in the pharmacy context, providing major benefits to pharmacies and patients.